Pathological Significance and Prognostic Roles of Indirect Bilirubin/Albumin Ratio in Hepatic Encephalopathy - Li, Yanling; Liu, Huiyuan; Chen, Keng; Wu, Xueheng; Wu, Jiawen; Yang, Zhenjun; Yao, Leyi; Wen, Guanmei; Zhang, Change; Chen, Xin; Chen, Xiaohui; Tang, Daolin; et al. (Frontiers in Medicine, 2021)
Background and Aim: The main hypotheses regarding the pathogenesis of hepatic encephalopathy (HE) include hyperammonemia, altered neurotransmission, and manganese toxicity et al., but the major factor for HE remains unclear due to unsuccessful clinical outcome. Methods: A retrospective case-control study of 204 patients with liver failure was conducted. Human serum albumin (HSA) or heme oxygenase-1 (HO-1) inhibitor SnPP(Tin protoporphyrin IX dichloride) was injected intraperitoneally into Ugt1-/- mice to establish a treatment model for endogenous hyperbilirubinemia. Results: IBil/albumin ratio (OR=1.626, 95%CI 1.323-2.000, P<0.001), white blood cell (WBC) (OR=1.128, 95% CI 1.009-1.262, P=0.035), ammonia (OR=1.010, 95%CI 1.001-1.019, P=0.027), platelet(PLT) (OR=1.008, 95%CI 1.001-1.016, P=0.022), Hb (OR=0.977, 95%CI 0.961-0.994, P=0.007), and PTA (OR=0.960, 95%CI 0.933-0.987, P=0.005) were independent factors of HE. Patients with a history of liver cirrhosis and severe HE (OR=12.323, 95%CI 3.278-47.076, P<0.001) were more likely to die during hospitalization. HSA or SnPP treatment improved cerebellum development and reduced cerebellum cell apoptosis. Conclusion: The IBil/albumin ratio constitutes the most powerful risk factor in the occurrence of HE, and reducing free bilirubin may be a new strategy for HE treatment. Besides, here we reported other novel independent risk factors (WBC, PLT, Hb) for HE.